2006
DOI: 10.3892/ijmm.18.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Cellular apoptosis susceptibility protein and proliferation in human hepatocellular carcinoma

Abstract: Abstract. The cellular apoptosis susceptibility protein (CAS) is the human homologue of the product of the essential yeast chromosome segregation gene, CSE1, and has important roles in tumor necrosis factor (TNF)-induced apoptosis and cell proliferation. In this study, we used immunoblotting and immunohistochemistry to look at CAS expression in human hepatocellular carcinoma (HCC) cells. We also sudied the correlation between CAS expression and cell proliferation. To do this, we studied the expression of proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Among the selected genes, PPIA 9 (peptidyl‐prolyl cis‐trans isomerase A), CDK4 26 and CSE1L 27 were shown to be upregulated in human HCC. CSE1L and CDK4 may play an important role in the development of HCC 28,29 . In contrast, RPL19 and GATA3 were overexpressed in human breast cancer 30 and pancreatic cancer, 31 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the selected genes, PPIA 9 (peptidyl‐prolyl cis‐trans isomerase A), CDK4 26 and CSE1L 27 were shown to be upregulated in human HCC. CSE1L and CDK4 may play an important role in the development of HCC 28,29 . In contrast, RPL19 and GATA3 were overexpressed in human breast cancer 30 and pancreatic cancer, 31 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…CSE1L and CDK4 may play an important role in the development of HCC. 28,29 In contrast, RPL19 and GATA3 were overexpressed in human breast cancer 30 and pancreatic cancer, 31 respectively. CDK4, RPL19, GATA3, CSE1L and APEX were shown to be prognostic markers.…”
Section: Differentially Expressed Genes In Woodchuck Hcc As Verified mentioning
confidence: 99%
“…Another study showed that the immunohistochemical staining intensity score of CSE1L was significantly higher in human hepatocellular carcinoma than in non-tumor tissue ( p < 0.05) [43]. In breast cancer, benign lesions of the breast showed weak CSE1L staining, while 70% - 90% of breast tumor cells were heavily stained for CSE1L [9].…”
Section: Introductionmentioning
confidence: 99%
“…Study also showed that the immunohistochemical staining intensity score of CSE1L was significantly higher in human hepatocellular carcinoma than in non-tumor tissue (p < 0.05) Shiraki et al, 2006).…”
Section: Prognosismentioning
confidence: 83%